In-barn measurements of surface roughness and friction of slatted concrete floors in sow gestation rooms. (May 2021) - Yan, Xiaojie; Zhang, Qiang; Connor, Laurie; Devillers, Nicolas; Dick, Kristopher
Abstract : Claw injuries of pigs due to inadequate floor surface conditions are a major concern in pig operations. Rough and slippery concrete floor surfaces can result in claw disorders. In this paper, the surface roughness and dynamic coefficient of friction (DCOF) of concrete floors used in two sow gestation rooms were studied. The first room had a slatted concrete floor with 105-mm wide slats and 19-mm wide gaps, and the second room had a floor with 125-mm wide slats and 25-mm wide gaps. A portable tester was designed and built to measure the surface roughness and friction of concrete floors. Measurements were conducted weekly during two gestation cycles for a total of 21 weeks. Based on the observations of sow activities, the floor in each room was virtually divided into four areas, namely dunging, high traffic, low traffic and sleeping areas. Surface roughness and friction were measured in the four areas in directions both parallel and perpendicular to the slats. The results showed that the length of time of floor usage by sows had a significant effect on the roughness and DCOF of concrete floors, with a sharp reduction in the DCOF after the first two weeks of use because manure stuck in the pores of the concrete surface reduced the interlocking between the asperities of the contact surfaces. No significant differences in the roughness and DCOF were found among different areas of floor (dunging, high traffic, low traffic and sleeping) or between the two floor configurations in the first 21 weeks of floor usage. Highlights: Friction & roughness of slatted concrete floor significantly affected by animal use. A sharp reduction in friction after 2 weeks due to manure in pores of floor surface. No significant differences in friction & roughness among different floor areas. No significant differences in friction & roughness between two floor configurations.